Professional master in teaching science and mathematics: an interpretation - Alberto Villani (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
An interpretation of the implementation and development of the Professional Masters in Science and Mathematics Education is displayed. In the survey of the events related to the project is pointed out that they cannot be understood only as fruits of neutral rational choices, but must also be understood as a result of political struggles in the academic field among three groups: the researchers in Science, the researchers in Education and the researchers in Science and Mathematics Teaching.